2004
DOI: 10.1148/radiol.2312021393
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Disease Assessment in Cystic Fibrosis: Comparison of CT Scoring Systems and Value of Bronchial and Arterial Dimension Measurements

Abstract: Thin-section CT scores were reproducible and were correlated with PFT results. Measurements of bronchial dimensions were not significantly related to scores or PFT results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
101
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 22 publications
9
101
0
5
Order By: Relevance
“…(1, 3,17) In parallel with the identification of the most prevalent changes, the results of the present study demonstrated that the use of a semiquantitative scoring system to detect pulmonary abnormalities on HRCT scans from patients with CF allows good overall intraobserver and interobserver agreement, demonstrating that the measurements are reproducible and reliable. We found good interobserver agreement for the total score and for three HRCT findings, namely acinar nodule, severity of bronchiectasis, and extent of bronchiectasis.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…(1, 3,17) In parallel with the identification of the most prevalent changes, the results of the present study demonstrated that the use of a semiquantitative scoring system to detect pulmonary abnormalities on HRCT scans from patients with CF allows good overall intraobserver and interobserver agreement, demonstrating that the measurements are reproducible and reliable. We found good interobserver agreement for the total score and for three HRCT findings, namely acinar nodule, severity of bronchiectasis, and extent of bronchiectasis.…”
supporting
confidence: 57%
“…(3) Chest HRCT is an imaging method that is considered specific for early evaluation of involvement of the lung parenchyma, as well as of the proximal and distal airways (bronchial wall thickening, bronchiectasis, mucoid impaction, and lung hyperinflation). (4) Reproducible scoring systems can be used in order to quantify CT findings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are concordant with analyses from other studies in which the three most prevalent abnormalities were bronchiectasis (86-90%), peribronchial thickening (53-80%) and mucous plugging (63-79%). 11,[26][27][28] In the present study, the modified Bhalla score values demonstrated that MRSA patients showed greater structural lung damage Although the other more prevalent injuries, such as peribronchial thickening, mucous plugging and mosaic perfusion, are known to be reversible, these were also more frequent in the MRSA group.…”
Section: Discussionsupporting
confidence: 53%